Comparison of Tramadol Infusion Versus Tramadol Boluses for Postoperative Pain in Patients Undergoing Lower Abdominal Surgeries - Muhammad Idrees, Iram Shahzadi, Maryam Sultana, Hasnain Ameer Hamza (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The management of postoperative pain is one of the primary focuses in efforts to reduce postoperative morbidity. Analgesia that is managed by the patient is a superior method for pain treatment since it eliminates the risk of both drug overdose and addiction. Objective: To compare the outcome with tramadol infusion versus tramadol boluses in patients undergoing lower abdominal surgeries. Design: It was a randomized controlled trial. Study Settings: Department of Anesthesiology, Doctor’s Hospital and Medical Centre, Lahore from from 21-06-2020 to 20-12-2020. Material and Methods: Using a random number table, the patients were divided equally between two groups. At the time of induction of general anaesthesia, patients in both groups received an initial loading dose of 1mg/Kg of tramadol through intravenous injection. While the infusion group had a tramadol infusion at 10mg/hr for 24 hours following surgery, the bolus group received a placebo solution (normal saline 0.9%) and patients only got boluses of 25 mg of tramadol on demand (VAS > 4) for up to 24 hours.. Patients were asked to complete a postoperative pain assessment after 24 hours had passed since surgery. When the VAS score was higher than 4, it was noted that analgesics were used. Results: In Group-A, the mean pain score in the sixth hour was 5.42±0.61 while in Group-B, it was 5.30±1.18. At the 12th hour, Group A was at 5.60 ±0.99 and Group B was at 5.08 ±1.60. At the 18th hour, Group A was at 4.90± 1.37 and Group B was at 5.26± 1.16. At the 24th hour, Group A was at 4.28± 1.68 and Group B was at 5.02 ±1.12. Mean analgesia was 60.00±0.00 in group A and 61.64±14.68 in group B at the sixth hour (P>0.05). At the 12-hour mark, group A’s mean analgesia was 117.50±11.88 and group B’s was 104.80±21.88 (P 0.05). There was no statistically significant difference in analgesic consumption between the treatment groups at the 18th and 24th hours (p-values: 0.120 and 0.929 respectively). Conclusion: In patients having lower abdominal operations, both tramadol administration methods are equally beneficial in reducing pain and analgesic use. Keywords: Tramadol boluses, Tramadol Infusion, General Anaesthesia, Lower Abdominal Surgeries